Metallophilic fungi research: an alternative for its use in the bioremediation of hexavalent chromium - García Hernández, María de los Ángeles; Villarreal Chiu, Juan Francisco; Garza González, María Teresa (2017)
Contamination by hexavalent chromium has had a large impact on modern society and human health. This problem is a consequence of its great industrial applicability to several products and processes. Short-term exposure to hexavalent chromium can cause irritation, ulceration in skin and stomach and in addition to cancer, dermatitis, and damage to liver, renal circulation and nervous tissues, with even death being observed in response to long-term exposures. Many techniques have been used for the remediation of this pollutant, including physical and chemical approaches and, in more recent years, biological methods. Filamentous fungi isolated from contaminated sites exhibit a significant tolerance to heavy metal; hence, they are an important source of microbiota capable of eliminating hexavalent chromium from the environment. However, these microorganisms can do so in different ways, including biosorption, bioreduction, and bioaccumulation, among others. In this review, we explore several of the most documented mechanisms that have been described for fungi/hexavalent chromium interactions and their potential use in bioremediation.